2019
DOI: 10.1101/865220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On deleterious mutations in perennials: inbreeding depression, mutation load and life-history evolution

Abstract: In Angiosperms, perennials typically present much higher levels of inbreeding depression than annuals. Two hypotheses have been proposed to explain this pattern.Because plants do not have a segregated germline, the first hypothesis states that more long-lived species may accumulate more somatic mutations as they grow, which they could then transmit to their offspring and thereby generate higher inbreeding depression. The second hypothesis, which does not contradict the first, stems from the observation that in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…only empirical test of Scofield & Schultz's [7] idea. Besides, recent theoretical investigations have shown that variations in inbreeding depression can in principle be generated by differences in the fitness effect of mutations between species with contrastring life histories [11], so that somatic mutations accumulation may not always be needed to explain variations in the magnitude of inbreeding depression across plant species. Moreover, theoretical investigations of the population-level consequences of somatic mutations accumulation are lacking, so that their role in the maintenance of high inbreeding depression in long-lived species remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…only empirical test of Scofield & Schultz's [7] idea. Besides, recent theoretical investigations have shown that variations in inbreeding depression can in principle be generated by differences in the fitness effect of mutations between species with contrastring life histories [11], so that somatic mutations accumulation may not always be needed to explain variations in the magnitude of inbreeding depression across plant species. Moreover, theoretical investigations of the population-level consequences of somatic mutations accumulation are lacking, so that their role in the maintenance of high inbreeding depression in long-lived species remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…This is however, to our knowledge, the only empirical test of Scofield and Schultz (2006)'s. Besides, recent theoretical investigations have shown that variations in inbreeding depression can in principle be generated by differences in the fitness effect of mutations between species with contrastring life-histories (Lesaffre and Billiard, 2020), so that somatic mutations accumulation may not always be needed to explain variations in the magnitude of inbreeding depression across plant species. Moreover, theoretical investigations of the population-level consequences of somatic mutations accumulation are lacking, so that their role in the maintenance of high inbreeding depression in long-lived species remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%